Metaphor Analysis on the Lyric of the Song "Hati-Hati di Jalan” by Tulus - Dea Septiani; Khairun Najmi; Putri Maulani Rahmadhita; Siti Nursa’adah; Syarifah Nurul Ma’rifah (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Metaphors are often found and or used in many literary works, one of which is song lyrics. This research was conducted with the aim of deciphering the types of metaphors contained in the lyrics of Tulus's song "Hati-Hati di Jalan". This research is a descriptive qualitative research type because the object of research is not in the form of numbers and is a document content, the object of this research is in the form of a type of expression and metaphorical meaning on the song "Hati-Hati di Jalan".Data collection techniques are by listening and recording techniques. Based on the results of research on the type of metaphorical expression and the meaning of metaphor expressions in the song "Hati-Hati di Jalan'' it can be concluded that (1) Types of metaphors found are 2 anthropomorphic metaphors (anthropomorphic metaphors) and three synesthetic metaphors. (2) The meaning of the metaphorical expression used is generally one line consisting of one meaning, but for related meanings, the data exists in one stanza.The use of this metaphor has been arranged so beautifully and neatly that the song can be enjoyed well and can affect the feelings of its listeners. This study aims to describe the type of metaphorical expression in one of the Sincere songs entitled "Hati-Hati di Jalan", and the metaphorical meaning of the song.